Extended depth of field in augmented reality - Sung Kyu Kim; Yongjoon Kwon; Ki-Hyuk Yoon (Scientific Reports, 2023)
Abstract The 3D display device shows an image with depth information. Conventional 3D display devices based on binocular parallax can focus accurately only on the depth of a specific screen. Because the human eye has a narrow depth of field (DOF) under normal circumstances, 3D displays that provide a relatively wide range of virtual depth areas have limitations on the DOF where clear 3D images are seen. To resolve this problem, it is necessary to find the optical conditions to extend the DOF and analyze the phenomena related to it. For this, by using the Rayleigh criterion and the Strehl ratio, a criterion for this extension of the DOF is suggested. A practical optical structure that can effectively extend the DOF is devised using a flat panel display. This optical structure could be applied to AR, VR, and MR in the field of near-eye displays. From the results of this research, the fundamental optical conditions and standards are proposed for 3D displays that will provide 3D images with extended DOF in the future. Furthermore, it is also expected that these conditions and criteria can be applied to optical designs for the required performance in the development of 3D displays in various fields.